My ChatQuiz System / Lok Wai Lay - Lok , Wai Lay (2003)
MY ChatQuiz system is a web-based application, which is developed with the aim to provide a user-friendly, attractive and interactive online learning environment to educational student to enhance their knowledge and communication among each other. The system is mainly focusing on secondary educational students as target users of the system. In general, MY ChatQuiz System consists of 4 main modules: Login module, chat module, quiz module and question bank management module. Surveys and reviews of various literatures have been conducted extensively to gain a better understanding of the project. The process modelling of project development is based on the Waterfall model with prototyping sub process. The system is designed based on good and essential features identified from existing system available on the Web in order to fulfill the functional and non-functional requirements. The system architecture of MY ChatQuiz System can be divided into client, web server and database server. The client, who is the web browser that can access information by connecting to the web server, it has to pass the request to the web server that will interact with the database. The database server processes the request and result is sent back to the web server and finally to the client. MY ChatQuiz System will be developed with combination of Java, JSP and Servlet technologies on Microsoft Windows 2000 platform utilizing database created by Microsoft Server 2000 since current client-server based database system will be migrate to web-based database system.